(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
This article explores the integration of artificial intelligence (AI) elements into English language teaching for future specialists, highlighting its transformative impact on language acquisition, adaptability, and real-world relevance. It discusses the benefits and challenges of AI-driven language instruction and emphasizes the importance of addressing the digital divide and maintaining a balance between AI and human interaction